SISTEM INFORMASI AKUNTANSI KEUANGAN KANTOR DESA TAMBAKREJO KENDAL METODE CASH BASIS - Sukemi Kamto Sudibyo; Eni Endaryati; Vivi Kumalasari Subroto; Sri Wahyuning; Nur Rokhman; Fitri Nur Romdhonah (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2024)
The Tambakrejo Village office has problems in managing village finances in recording and presenting financial reports. Currently, the Tambakrejo village office uses a manual reporting system by handwriting it in a book. Data is stored in archives which may be lost or damaged, requires a long time to search if the data is to be used or viewed again, delays in preparing village financial reports due to ineffective recording and management of financial reports. The aim of this research is to produce a Financial Accounting Information System Using the Cash Basis Method in Tambakrejo Kendal Village to help handle the recording and processing of village financial reports to make them more effective and computerized. Design and development of an accounting information system using the PHP and CSS bootstrap programming languages, MySQL as a database, with Research and Development research methods. The implementation of this system has been able to simplify the financial management process of the Tambakrejo Village Office so that financial reports are obtained more quickly, easily and effectively. The financial accounting information system of the Tambakrejo Kendal Village Office, the cash basis method, is useful for handling the process of recording, processing and reporting village cash finances based on proof of cash transactions when received or disbursed and is able to provide accurate information on village financial balances in the form of numbers and is equipped with digital archiving of proof of transactions.